The VHL tumor suppressor inhibits expression of the IGF1R and its loss induces IGF1R upregulation in human clear cell renal carcinoma. - Yuen, J; Cockman, M; Sullivan, M; Protheroe, A; Turner, G; Roberts, I; Pugh, C; Werner, H; Macaulay, V (2007)
Clear cell renal cell cancer (CC-RCC) is a highly chemoresistant tumor characterized by frequent inactivation of the von Hippel-Lindau (VHL) gene. The prognosis is reportedly worse in patients whose tumors express immunoreactive type I insulin-like growth factor receptor (IGF1R), a key mediator of tumor cell survival. We aimed to investigate how IGF1R expression is regulated, and found that IGF1R protein levels were unaffected by hypoxia, but were higher in CC-RCC cells harboring mutant inactive VHL than in isogenic cells expressing wild-type (WT) VHL. IGF1R mRNA and promoter activities were significantly lower in CC-RCC cells expressing WT VHL, consistent with a transcriptional effect. In Sp1-null Drosophila Schneider cells, IGF1R promoter activity was dependent on exogenous Sp1, and was suppressed by full-length VHL protein (pVHL) but only partially by truncated VHL lacking the Sp1-binding motif. pVHL also reduced the stability of IGF1R mRNA via sequestration of HuR protein. Finally, IGF1R mRNA levels were significantly higher in CC-RCC biopsies than benign kidney, confirming the clinical relevance of these findings. Thus, we have identified a new hypoxia-independent role for VHL in suppressing IGF1R transcription and mRNA stability. VHL inactivation leads to IGF1R upregulation, contributing to renal tumorigenesis and potentially also to chemoresistance.